Teleconference Dalam Proses Pengadilan Perspektif Hukum Islam - Andi Nur Wasita Syafirawati; A. Farah Salsabilah; Kurniati Kurniati (Ethics and Law Journal: Business and Notary, 2024)
Teleconferencing has emerged as a new legal innovation in the evidentiary process in court, where witnesses can provide testimony through this system. However, the Criminal Procedure Law, which functions as the legal framework for trials, does not yet include provisions related to this matter. Law Number 11 of 2008 concerning Information and Electronic Transactions is recognized as valid evidence, expanding the scope of evidence regulated in the Criminal Procedure Code. The aim of this research is to determine the role of evidence via teleconferencing in court, seen from the perspective of Islamic law. In this context, the concept of proof in Islamic law includes instructions (karinah) and witness testimony (shahadah) as evidence. It is hoped that this theoretical analysis can reveal how the system of evidence in Islamic criminal law has developed along with advances in technology. This research was prepared using the library research research method, namely research with library studies as the main reference material in research with a normative juridical and normative theological/syar'i approach. In the Islamic context teleconferencing can be considered as a means that facilitates efficient long-distance communication between individuals or groups. When delivering testimony via teleconference, it is important to ensure that communication is carried out in an ethical and polite manner, in accordance with Islamic ethical values such as politeness and honestyWrite your abstract here. Abstract contains a brieft introduction to the problem, objective of paper, and a brieft summary of discussion. Abstract is single-spaced typed in English 150-200 words. Written with Goudy Old Style (10 Pt) Italic. The abstract contains the background, problems, research methods, results of the discussion, as well as conclusions and suggestions. AbstrakTeleconference muncul sebagai inovasi hukum yang baru dalam proses pembuktian di pengadilan, di mana saksi dapat memberikan kesaksian melalui sistem tersebut. Meskipun demikian, Hukum Acara Pidana, yang berfungsi sebagai kerangka hukum dalam persidangan, belum mencakup ketentuan terkait hal tersebut. Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik diakui sebagai alat bukti yang sah, mengembangkan cakupan alat bukti yang diatur dalam Kitab Undang-undang Hukum Acara Pidana. Tujuan dari penelitian ini adalah untuk mengetahui peran pembuktian melalui telekonferensi di pengadilan, dilihat dari perspektif hukum Islam. Dalam konteks ini, konsep pembuktian dalam hukum Islam mencakup adanya petunjuk (karinah) dan kesaksian saksi (syahadah) sebagai alat bukti. Analisis teori ini diharapkan dapat mengungkapkan bagaimana sistem pembuktian dalam hukum pidana Islam telah mengalami perkembangan seiring dengan kemajuan teknologi. Penelitian ini disusun dengan meggunakan metode penelitian library research yaitu penelitian dengan studi pustaka sebagai bahan rujukan utama dalam penelitian dengan pendekatan yuridis normatif dan teologis normatif/syar’i. Dalam konteks Islam teleconference dapat dianggap sebagai sarana yang memfasilitasi komunikasi jarak jauh yang efisien antara individu atau kelompok. Dalam menyampaikan kesaksian melalui teleconference penting untuk memastikan bahwa komunikasi dilakukan dengan adab dan sopan, sesuai dengan nilai-nilai etika Islam seperti kesopanan dan kejujuran.